The status of literature in six types of Trinidad secondary schools: Issues, implications, and recommendations - James, Cynthia (School of Education, UWI, St. Augustine, 2003)
A survey of teachers' perspectives on the status of literature in Trinidadian secondary schools suggested that the subject is dying. Teachers cited problems with reading, critical thinking, and students' lack of interest, singling out poetry as an area of little competence. Current deficiencies in teaching strategies suggest that teachers need to approach the language arts, on the whole, as a field of knowledge, amenable to and requiring scientific methods of approach, which teachers must perfect. A comparative survey of students suggested that teachers need to take into consideration the allure that technology holds for young people in planning their lessons. They also need to be aware that the secondary school population of Trinidad and Tobago is not homogenous, and requires varied strategies and teaching approaches to woo its varied cultures. Further recommendations of this paper include: (a) the training of secondary school teachers of English in the teaching of reading and remedial reading strategies; and (b) a focus on literature in all its genres, including non-fiction, especially for the upper levels of public secondary schools, and particularly to attract boys. It is felt that these policies, together, will promote a culture that will offset the literacy problems that affect schools, as well as enhance the preparation for adulthood that schooling offers
Keywords: Literature education; Secondary schools; Trinidad and Tobago